Prevalence of Shiga Toxin-Producing and Enteropathogenic Escherichia coli in Wild and Pet Birds in Iran - A Koochakzadeh (Brazilian Journal of Poultry Science, 2015)
ABSTRACT The aim of this study was to investigate the prevalence of Shiga toxin-producing Escherichia coli (STEC) and enteropathogenic E. coli (EPEC) strains and to identify the stx gene types in wild captive and companion birds. In total,657 E. coli isolates from 219 birds belonging to 38 different species were investigated for the presence of STEC and EPEC strains. It was shown that five birds (2.28%) carried strains positive for one or more of the virulence factors investigated. The results indicated that 1.8% (n=4) and 0.45% (n=1) of the birds carried STEC and EPEC strains, respectively. All STEC strains harbored the stx2f and eae genes and this finding reveals the role of other birds, in addition to pigeons, as reservoirs of STEC. The only EPEC strain in this study was isolated from a Myna. Based on our knowledge, this is the first report of Stx2f-producing STEC in Geese, Duck and Lesser kestrel. In conclusion, the results indicate a low frequency of STEC carriage in wild and companion birds, and point out the need of additionally screening for the presence of stx2f in all the eae-harboring strains from birds.